2015
DOI: 10.1080/1756073x.2015.1105089
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Type Profile and Work-Related Psychological Health of Clergy Serving in the Diocese of Chester

Abstract: This study examines the psychological type profile and work-related psychological health of 99 clergy serving the Diocese of Chester alongside normative data for the Church of England published in previous studies. The data demonstrated that these clergy share the general psychological type profile of Church of England clergy, with preferences for introversion (60%), intuition (55%), feeling (57%), and judging (76%). Compared with the normative data they show slightly better work-related psychological health, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A third pilot study reported by Francis, Ratter and Longden also came to similar conclusions, 19 drawing on a 50 per cent response rate from clergy within one Church of England Diocese who completed the Francis Psychological Type Scales. This study focused only on clergy who had served the same church for at least five years and compared the psychological type continuous scale scores of 29 clergy whose congregations had declined over the past six years with 19 clergy whose congregations had grown over that period.…”
Section: Per Cent Of Clergy Who Preferred Extraversion and Intuition Voas And Watt Concludedmentioning
confidence: 56%
“…A third pilot study reported by Francis, Ratter and Longden also came to similar conclusions, 19 drawing on a 50 per cent response rate from clergy within one Church of England Diocese who completed the Francis Psychological Type Scales. This study focused only on clergy who had served the same church for at least five years and compared the psychological type continuous scale scores of 29 clergy whose congregations had declined over the past six years with 19 clergy whose congregations had grown over that period.…”
Section: Per Cent Of Clergy Who Preferred Extraversion and Intuition Voas And Watt Concludedmentioning
confidence: 56%
“…Studies employing the (Maslach & Jackson, 1986) model of burnout among Anglican clergy serving in the Church of England or the Church in Wales have been reported by Francis and Rutledge (2000), Rutledge and Francis (2004), Hills et al (2004), Francis andTurton (2004a, 2004b), Randall (2004Randall ( , 2005Randall ( , 2007Randall ( , 2013a, and Turton and Francis (2007). Studies employing the (Francis, Village, Robbins & Wulff, 2011) model of burnout among Anglican clergy serving in the Church of England or the Church in Wales have been reported by Robbins and Francis (2010), Brewster et al (2011), Randall (2013a, 2013b, 2015, Francis, Payne, et al (2013), Francis et al ( , 2017, Francis, Ratter, et al (2015), Village et al (2018), Francis, Emslie, et al (2019), and Francis, Laycock, et al (2019). Set within the broader context of international studies employing the same measures of work-related psychological health and wellbeing, a number of conclusions can be drawn regarding the correlates, antecedents, and consequences of poor work-related psychological health among clergy (see Francis, 2018).…”
Section: Introductionmentioning
confidence: 99%